Tortura: testemunhos de um crime demasiadamente humano - Arantes, Maria Auxiliadora de Almeida Cunha (2011)
This work aims at the theoretical approach of torture as a practice that runs through and remains in the history of humans. The sustainment of torture through the ages, despite the continuous process of cultural development, presupposes the existence of an intrinsic obstacle to the humans that prevents its exclusion from the realm of civilization. The search of the obstacle to the ultimate eradication of torture is the main objective of this work. Being essentially a human practice, the theoretical framework consists of the Freudian texts referring to culture and texts of contemporary thinkers who wrote about the cruelty and destructiveness as intrinsic to the relations between men. The approach to torture has been possible from testimonies and narratives of events where this was an extreme practice. The work focuses on the testimony of former political prisoners tortured during the civil-military dictatorship in Brazil and adds information about the state of exception that prevailed during this period. The reference to history is adressed through events at different times, which makes evident that the practice is age-old, despite the civilizational efforts to prohibit it. In the closing remarks, are expressed the main conclusions: torture is an act that only humans do and practice throughout history; the torturer who exercises it is fully aware of what is and therefore is responsible for his crime of extreme cruelty; and finally, the finding that the psychic inscription of torture cannot be erased, for nothing that once formed can perish